Talking back: senior scholars and their colleagues deliberate the past, present, and future of writing studies - Elliot, Norbert, editor; Horning, Alice S., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2020)
Prestigious writing studies scholars deliberate on intellectual traditions, current practices, and directions for the future. Mid-career scholars react to each chapter with a thoughtful and measured response. Authors have three common experiences: responsibility for advancing a profession, research dedicated to advancing opportunities, and a sense of humility.--Provided by publisher.
The professionalization and future of technical and professional communication / Jo Allen; response: Turning towards social justice approaches to technical and professional communication / Michele F. Eble -- Talking brought me here: sociolinguistics and African American life / Akuda Duku Anokye; response: Still talking: embracing varieties, worlds Englishes, and the power of words / Patricia Friedrich -- The times, they are a-changin': one assessment specialist's reflections on the evolution of research and policy in large-scale assessments at one assessment company / Douglas Baldwin; response: You better start swimmin' or you'll sink like a stone: how assessment keeps changin' / Devon Tomasulo -- Learning from the National Writing Project as a kindergarten-university partnership: talking back and forth / Judy Buchanan and Richard Sterling; response: Talking back and forth between memory and legacy in the National Writing Project /Anne Elrod Whitney -- Intimate machines: cultivating wisdom in elder gardens / Hugh Burns; response: Toward a research agenda for digital intimacy / Ann N. Amicucci -- Assessment as a by-product of ongoing research: identifying, describing, and nourishing a campus culture of teaching and learning / William Condon; Reponse: From assessment as research to empirical education / Mike Truong -- A Bedford story: taking the measure of a publisher / Joan Feinberg; response: On being useful / Leasa Burton -- Framing and facing histories of rhetoric and composition: composition-rhetoric in the time of the Dartmouth conference / Cinthia Gannett and John C. Brereton; response: History has moved through us / Katherine E. Tirabassi -- Wisdom: a meditative quilt / Eli Goldblatt; response: Doors, walls, and the paradox of not knowing / Jessica Restaino; response: Legacy and invitation / Paige Davis Arrington, with Ann E. Berthoff -- "Bottomless mysteries" on the margins: a dream interview / Janis Haswell and Richard Haswell; response: Toward open exchanges in a networked world / Stacey Pigg -- Aging through the thirty-year rise of professionalized writing administration / Douglas Hesse; response: Embracing the accidental trajectory / Eliana Schonberg -- Reading old and new: an autobiography and an argument / Alice S. Horning; response: Talking back (to Alice S. Horning) / Ellen Carillo -- Rewriting the language(s) of language differences in writing / Min-Zhan Lu and Bruce Horner; response: Not trajectory but translation: talking back with and to Min-Zhan Lu and Bruce Horner / Dylan B. Dryer -- Starting from scratch: practicing and teaching the work of words / Donald McQuade; response: The goal of teaching is to become obsolete / Eric Heltzel -- Rethinking basic writing: reflections on language, education, and opportunity / Rebecca Williams Mlynarczyk; response: A reckoning for basic writing / Sean Molloy -- Contact zones across the disciplines / Les Perelman; response: Writing research across disciplinary boundaries / Suzanne Lane -- Identity work: continuities and transformations in the senior years / Louise Wetherbee Phelps; response: Reading identity work through a disability lens: care, bodies, and time / Elisabeth L. Miller -- Raciolinguistics and the "Mis-education of the negro" -- and you too: race, language, and the elder in "post-racial" America / Geneva Smitherman; response: "I love my African American language. And Yours": toward a raciolinguistic vision in writing studies / Shenika Hankerson -- Valuing new approaches for tenure and promotion for WAC/WID Scholar/Administrators: advice for higher education and the writing studies community / Martha A. Townsend; response: Community: a response to Marty Townsend / Michael Rifenburg -- Mode meshing: before the new world was new / Victor Villanueva; response: Becoming in the new world / Asao B. Inoue -- Fifty years of curriculum changes: looking in and looking out in college writing classes / Edward M. White; response: Looking back to move forward: a response to Edward M. White / Sherry Rankins-Robertson -- The composing of seniors: navigating needs, tasks, and social practices / Kathleen Blake Yancey; response: The composing of the 41%: a response to Kathleen Blake Yancey / Jennifer Enoch.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); Academic writing -- Study and teaching; Composition (Language arts) -- Study and teaching